Relatively high light inhibits reserves degradation in the Coptis chinensis rhizome during the leaf expansion by changing the source-sink relationship - Ke, Wenjia; Li, Yirou; Zhong, Furong; Pen, Maoyao; Dong, Jijing; Xu, Binjie; Ma, Yuntong; Zhou, Tao (Frontiers in Plant Science, 2023)
The early spring is a seasonal high-light "window" for new leaf growth and photosynthetic carbon capture of the shade-tolerant evergreen understory plants. However, it remains unclear how light regulates the source-sink relationship between rhizome (RO), mature leaf (ML), and immature leaf (IL) during Coptis chinensis leaf expansion. Understanding this relationship is essential to reduce RO reserve degradation and ultimately promote RO biomass accumulation.The plants grew in artificial climate chamber with low (50 μmol m -2 s -1 ) and relatively high (200 μmol m -2 s -1 ) light intensity treatments. Leaf fluorescence, foliar P fractions, soluble sugars, starch, total P, and alkaloids concentration in ILs, MLs, and RO were measured and 13 C labeling was used to indicate the direction of photosynthetic carbon flow between organs.Y(II), rETR,qP, and sucrose and glucose, in ILs and MLs under relative high light was higher than those under low light. The glucose and starch concentration in ILs at 35 days was significantly higher than that at 15 days when plants under 200 , while they were not significantly changed and remained low level under 50. The 13 C was detected in the RO when plants were grown at 200, regardless of ILs and MLs 13 C-labeling, while no 13 C was detected in the RO when plants under 50.Total P concentration in ILs was lower under relatively high light, but there was no difference in nucleic acids P concentration in ILs under the two light intensity treatments. We propose that relatively high light reduces the need for carbohydrate and P stored in the RO to support ILs growth by (1) accelerating the sink to source transition in ILs, which inhibits the use of reserves in the RO, (2) using energy from MLs to support ILs growth, thereby reducing RO reserves consumption, and (3) reducing the demand for P by investing less in the development of photosynthetic machinery. Furthermore, under low light, MLs serve as a sink and rely on other organs for support, directly or indirectly exacerbating the reserves lost in the RO.